ANALISA PENGARUH PERILAKU U-TURN PADA KINERJA LALU LINTAS PADA JALAN PERKOTAAN (STUDI KASUS: JL. JENDERAL SUPRAPTO) - Madani, Ananda Putera Novian Milleandra; Widyastuti, Hera (Rang Teknik Journal, 2026)
U-turn planning is regulated by several Indonesian regulations, such as the Regulation on Separator Planning Procedures No. 014/T/BNTK/1990, the Specification for Lane Separator Openings, SKSNIS-04-1990 F, and the U-Turn Planning Module (U-Turn Planning Guidelines), No. 06/BM/2005. According to these regulations, u-turns cannot be too wide or too narrow, and the number of u-turns on a single road section is also regulated, as is their position. Therefore, in this context, u-turns are not always a solution for traffic efficiency. They can be a nuisance if not properly planned. The analysis was conducted in several stages. First, a visual calculation was performed to determine the average delay caused by the u-turn. Second, an appropriate traffic model was found to obtain traffic parameters and predict future traffic events. The traffic model was determined using linear regression and selected using the chi-square test. Third, calculate the traffic parameters if the delays identified in the first stage are removed, then compare the parameters from the first stage (where delays are present) with the parameters from the third stage (where delays are absent). The initial hypothesis in this study is that delays will positively impact traffic performance. This is based on the results of previous research mentioned above. Keywords: u-turn, traffic performance, delay, traffic model, regression